2021
DOI: 10.1002/cfp2.1129
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in COVID‐19‐related stress and relationships with life satisfaction among financial advisors

Abstract: This study examines gender differences in COVID-19-related stress and the relationship between COVID-19-related stress and life satisfaction in a large sample of financial advisors in the United States (n = 499). Compared to men, women reported greater increases in work-related stress since the onset of COVID-19, higher levels of stress from managing family responsibilities, and more stress from witnessing the impact of COVID-19 on their clients (i.e., empathetic stress). Using an integrative model of top-down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
5
1
Order By: Relevance
“…Our results demonstrated that patients have high to very high levels of stress, which are associated with a strong positive correlation with salivary biomarkers. We found no statistical dependence of stress level on age, gender, or diagnosis, despite data reported from global surveys where higher levels of stress were associated with younger age and female gender ( 9 , 46 ). Rather, these differences may be due not so much to gender and age as to the influence of other environmental factors—socioeconomic, professional and/or family responsibilities, education, and others.…”
Section: Discussioncontrasting
confidence: 96%
“…Our results demonstrated that patients have high to very high levels of stress, which are associated with a strong positive correlation with salivary biomarkers. We found no statistical dependence of stress level on age, gender, or diagnosis, despite data reported from global surveys where higher levels of stress were associated with younger age and female gender ( 9 , 46 ). Rather, these differences may be due not so much to gender and age as to the influence of other environmental factors—socioeconomic, professional and/or family responsibilities, education, and others.…”
Section: Discussioncontrasting
confidence: 96%
“…According to Almeida et al (2020), Czeisler et al (2020), Pérez et al (2021), Pieh et al (2020), andSediri et al (2020), these and other functions that have been associated with the gender role have caused women to experience high levels of anxiety and stress. Although this research did not investigate whether compliance with activities attributed to the gender role was related to stress, studies and reports carried out during the first phases of the pandemic have indicated that the mental health of women has deteriorated significantly, due to the increase in work and domestic tasks they perform (Pérez et al, 2021;Rodríguez-Bermúdez et al, 2021;Tharp et al, 2021). Concerning the coping evaluation, it was found that in all the subscales the participants scored below the average, even in the positive factor positive reappraisal, this result suggests that they have an active coping not only with specific stressors but also in those that arise in the normal course of the pandemic (Capasso et al, 2021;Parisi et al, 2021;Pérez et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out by Pérez et al (2021) revealed that the most frequent emotional responses in a sample of 174 Mexican women (M = 37.72 years) were anxiety and stress, 72.4% of the women requested psychological support to attend to psychosocial needs at the beginning of the Nueva Normalidad stage due to interpersonal problems and task overload. Tharp et al (2021) found that socioeconomic status and marital status are not variables that are related to stress, however, the gender role is due to the activities expected in men and women. Other studies reveal that perception of less stress is related to greater resilience and the implementation of adaptive coping styles, in addition to other variables such as educational level and the professional situation in the case of women (Abbott et al, 2021;Lindinger-Sternart et al, 2021).…”
Section: Introductionmentioning
confidence: 96%
“…Research on COVID-19 pandemic revealed that women have experienced greater stress (Mazza et al, 2020 ) and increased domestic responsibilities (Andrew et al, 2020 ) compared to men since the onset of the COVID‐19 (Mazza et al, 2020 ). Some studies indicated that COVID‐19‐related stress was a significant predictor of life satisfaction for women but not men (e.g., Tharp et al, 2021 ). Past studies showed that women reported higher levels of extradyadic stress from daily hassles and intradyadic stress from relationship problems as well more symptoms of depression and anxiety (Falconier et al, 2015 ; Neff & Karney, 2005 ).…”
Section: Discussionmentioning
confidence: 99%